Associations Between Vascular Risk Factor Levels and Cognitive Decline Among Stroke Survivors - Deborah A. Levine; Bingxin Chen; Andrzej T. Gałecki; Alden L. Gross; Emily M. Briceño; Rachael T. Whitney; Robert Ploutz‐Snyder; Bruno Giordani; Jeremy B. Sussman; James Burke; Ronald M. Lazar; Virginia J. Howard; et al. (2023)
Importance Incident stroke is associated with accelerated cognitive decline. Whether poststroke vascular risk factor levels are associated with faster cognitive decline is uncertain. Objective To evaluate associations of poststroke systolic blood pressure (SBP), glucose, and low-density lipoprotein (LDL) cholesterol levels with cognitive decline. Design, Setting, and Participants Individual participant data meta-analysis of 4 US cohort studies (conducted 1971-2019). Linear mixed-effects models estimated changes in cognition after incident stroke. Median (IQR) follow-up was 4.7 (2.6-7.9) years. Analysis began August 2021 and was completed March 2023. Exposures Time-dependent cumulative mean poststroke SBP, glucose, and LDL cholesterol levels. Main Outcomes and Measures The primary outcome was change in global cognition. Secondary outcomes were change in executive function and memory. Outcomes were standardized as t scores (mean [SD], 50 [10]); a 1-point difference represents a 0.1-SD difference in cognition. Results A total of 1120 eligible dementia-free individuals with incident stroke were identified; 982 (87.7%) had available covariate data and 138 (12.3%) were excluded for missing covariate data. Of the 982, 480 (48.9%) were female individuals, and 289 (29.4%) were Black individuals. The median age at incident stroke was 74.6 (IQR, 69.1-79.8; range, 44.1-96.4) years. Cumulative mean poststroke SBP and LDL cholesterol levels were not associated with any cognitive outcome. However, after accounting for cumulative mean poststroke SBP and LDL cholesterol levels, higher cumulative mean poststroke glucose level was associated with faster decline in global cognition (−0.04 points/y faster per each 10–mg/dL increase [95% CI, −0.08 to −0.001 points/y]; P = .046) but not executive function or memory. After restricting to 798 participants with apolipoprotein E4 (APOE4) data and controlling for APOE4 and APOE4 × time, higher cumulative mean poststroke glucose level was associated with a faster decline in global cognition in models without and with adjustment for cumulative mean poststroke SBP and LDL cholesterol levels (−0.05 points/y faster per 10–mg/dL increase [95% CI, −0.09 to −0.01 points/y]; P = .01; −0.07 points/y faster per 10–mg/dL increase [95% CI, −0.11 to −0.03 points/y]; P = .002) but not executive function or memory declines. Conclusions and Relevance In this cohort study, higher poststroke glucose levels were associated with faster global cognitive decline. We found no evidence that poststroke LDL cholesterol and SBP levels were associated with cognitive decline.